Pengaruh Corporate Governance terhadap Tax Avoidance - Veren Chintia; Yulius Kurnia Susanto (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research was to obtain empirical evidence of 7 independent variables and 1 dependent variable. Executive compensation, executive character, company size, institutional ownership, the proportion of BOC, audit committee, and audit quality are the company's independent variables that affect tax avoidance which is the dependent variable.The objects used in this research is all manufacturing companies listed in Indonesia Stock Exchange (IDX) during the research period 2018 to 2020. The samples used in this study were 49 companies that were selected through purposive sampling with a total of 147 data. In this reaserch to test the hypothesis must using multiple regression analysis.The results shown in this research are company size and audit quality variables have an influence on tax avoidance. Meanwhile, the variables of executive compensation, executive character, institutional ownership, the proportion of BOC, and audit committee do not have any influence on tax avoidance. The larger company size, the higher the possibility of the company in doing tax avoidance.